2002
DOI: 10.1136/thorax.57.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and function of the peptide transporter PEPT2 in normal and cystic fibrosis human lung

Abstract: Background: Aerosol administration of peptide based drugs has an important role in the treatment of various pulmonary and systemic diseases. The characterisation of pulmonary peptide transport pathways can lead to new strategies in aerosol drug treatment. Methods: Immunohistochemistry and ex vivo uptake studies were established to assess the distribution and activity of the β-lactam transporting high affinity proton coupled peptide transporter PEPT2 in normal and cystic fibrosis human airway tissue. Results: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 44 publications
(38 reference statements)
2
34
1
1
Order By: Relevance
“…Previous work has shown that MDP is a substrate for PEPT1, a paralogous member of the SLC15A proton oligopeptide transporter family (20). Interestingly, PEPT2 is abundantly expressed throughout the respiratory tract by epithelia and PEPT1 is not (10), whereas the opposite holds true of the gut epithelium. Taken with our findings, we contend that MDP was not immunoreactive due to a lack of cell uptake by lung epithelia.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous work has shown that MDP is a substrate for PEPT1, a paralogous member of the SLC15A proton oligopeptide transporter family (20). Interestingly, PEPT2 is abundantly expressed throughout the respiratory tract by epithelia and PEPT1 is not (10), whereas the opposite holds true of the gut epithelium. Taken with our findings, we contend that MDP was not immunoreactive due to a lack of cell uptake by lung epithelia.…”
Section: Discussionmentioning
confidence: 79%
“…PEPT2 displays promiscuous ligand affinity and mediates, in addition to its natural di-and tripeptide substrates, the uptake of numerous peptidomimetic drug molecules, such as b-lactam antibiotics and antivirals. Our previous work and that of others characterized PEPT2 expression and function in humans in situ in bronchial, bronchiolar, and alveolar type II epithelial cells (9)(10)(11). We first reported the functional characterization of PEPT2-mediated transport across the apical surface of fully differentiated, polarized, primary human upper airway epithelial cultures (hUAECs, henceforth referred to as human lung epithelial cells [hLECs]).…”
mentioning
confidence: 99%
“…PEPT would act by decreasing the drug concentration within ELF by uptake into epithelial cells. Yet, the mechanism describing how drugs leave pulmonary cells has not been characterized (41,42). Further studies are necessary to characterize the functions of OCTs and PEPT in the transport of colistin at the air-blood barrier level, since this in vivo study could not address this issue.…”
Section: Discussionmentioning
confidence: 93%
“…221 PEPT 2 and more recently PEPT 1 were detected first in the airway epithelium and then in the bronchial epithelium. 222,223 These two transporters have also been found in animals and cell lines. 224,225 However, how they interact with drug formulations and their activity in respiratory diseases 226 has not been fully investigated.…”
Section: Peptide Transportersmentioning
confidence: 96%